2019
DOI: 10.1186/s13017-019-0223-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial embolization versus surgery for refractory non-variceal upper gastrointestinal bleeding: a meta-analysis

Abstract: BackgroundNowadays, very few patients with non-variceal upper gastrointestinal bleeding fail endoscopic hemostasis (refractory NVUGIB). This subset of patients poses a clinical dilemma: should they be operated on or referred to transcatheter arterial embolization (TAE)?ObjectivesTo carry out a systematic review of the literature and to perform a meta-analysis of studies that directly compare TAE and surgery in patients with refractory NVUGIB.Materials and methodsWe searched PubMed, Ovid MEDLINE, and Embase. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 37 publications
0
40
0
4
Order By: Relevance
“…A significantly lower rate of post-procedural complications was reported in the angioembolization cohort. The latest meta-analysis [137] found similar results, but interestingly found a slight drift toward a lower mortality for the angioembolization group.…”
Section: Angiography Embolizationmentioning
confidence: 61%
See 1 more Smart Citation
“…A significantly lower rate of post-procedural complications was reported in the angioembolization cohort. The latest meta-analysis [137] found similar results, but interestingly found a slight drift toward a lower mortality for the angioembolization group.…”
Section: Angiography Embolizationmentioning
confidence: 61%
“…One prospective and multiple retrospective cohort studies comparing outcomes between patients undergoing angioembolization with those undergoing surgery for rebleeding after failed endoscopic control are available. These studies were summarized in three meta-analysis [135][136][137]. Kyaw et al summarized 6 retrospective cohort studies: surgery was found to significantly reduce the likelihood of further (post-intervention) hemorrhage, and was associated with a trend towards a reduced need for further intervention.…”
Section: Angiography Embolizationmentioning
confidence: 99%
“…Few RCTs have compared alternative treatment modalities in the management of patients with persistent ulcer bleeding. Meta-analyses and retrospective case series comparing transcatheter arterial embolization (TAE) and surgery suggest that patient outcomes following either approach are similar [127][128][129]. TAE, however, is associated with a higher failure rate in the control of bleeding [127][128][129] [132].…”
Section: Recommendationmentioning
confidence: 99%
“…Transcatheter arterial embolization (TAE) is widely acknowledged for its effectiveness in treating brisk arterial bleeding 20 . It has largely replaced surgery as a rst-line therapy for UGIB refractory to endoscopic treatment due to its high e cacy and favorable safety pro le 21 . However, a subgroup of ulcers remains at high-risk of future rebleeding despite achieving hemostasis via endoscopy.…”
Section: Discussionmentioning
confidence: 99%